Influence of Coaching on Employee Retention in Commercial Banks in Kenya - Kamunya, Magdalene; Nzulwa, Dr. Joyce (Human Resource and Leadership Journal, 2020)
Purpose: The main objective of the study was to determine the influence of employee coaching on employee retention in commercial banks. The study specifically aimed to determine the influence of performance coaching, career coaching, life skills coaching and executive coaching on employee retention in commercial banks. Methodology: The study adopted a descriptive research design and the target population comprised of a total of 306 staff working in the six selected Commercial Banks in Kenya. The selected commercial banks included; Cooperative bank of Kenya Ltd; Kenya Commercial Bank Ltd; Consolidated bank of Kenya Ltd; Standard Chartered bank Kenya Ltd and CFC Stanbic Bank Ltd and NIC bank. The study adopted a probability sampling design by using a stratified random sampling technique to select the sample size of 136 respondents. Questionnaires were used as the main data collection instruments and pretested for validity and reliability using a pilot study. Data gathered was analyzed using both descriptive and inferential statistics and presented using tables and charts. Findings: The study findings indicated that performance coaching factors notably, goal setting, feedback, personal development and goals achievement influences employee's retention in commercial. The study also noted that career coaching ensured that employee personal interests are considered, employee career expectations are met there is achievement of employee personal goals and employees are able to effectively plan their careers. The study concluded that performance coaching is the major coaching method that influences most employee retention in commercial banks, followed by career coaching, then executive coaching and lastly life skills coaching. Unique contribution to theory, practice and policy: The study recommends that to improve on performance coaching, the bank management should offer performance coaching programmes which equips employees with skills to enable employees to understand organization goals and set their goals and work towards achievement of the goals. The bank management should adopt effective career coaching programmes which motivate employees to stay working in the organization in order to advance their careers. The bank management should provide coaching programmes which ensures that employee personal interests are considered, employee career expectations are met and there is achievement of employee personal goals and employees are able to effectively plan their careers. This will contribute towards employee career development and growth which influences most employees to remain working in organization and hence leading to increased rate of retention